Much ado about nothing - Shakespeare, William, 1564-1616 (Staged collection., 2024)
"Love, deception and discord are flourishing in the court of Messina. Sweet, innocent Hero and the famed soldier Claudio are immediately infatuated, while the bickering Beatrice and Benedick can agree on just one thing: the other is insufferable. Little do they know, two plans are afoot - one to make Beatrice and Benedick fall in love, another to break up Hero and Claudio"--Amazon.com.